Thematic Qur’anic of the Mīzān Verse: Constructing an Islamic Ecotheological Paradigm in Preventing Environmental Destruction: - - Acep Ariyadri; Muhammad Sapil; Aisyah Abdul Hasib; Fauzan Syarif Nursyafi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
This study aims to construct an Islamic ecotheological paradigm to serve as a theological framework for preventing fasād (destruction), based on a thematic interpretation of the mīzān (balance) verses in the Qur'an. Methodologically, this study employs a qualitative approach utilizing Abd al-Hayy al-Farmawī’s thematic Qur’anic (mawdūʿī) framework. The analytical steps involve aggregating relevant verses on mīzān, tracing their contextual meanings, establishing correlations (munāsabah), and synthesizing these textual insights into a structured ecological concept. The results indicate that the mīzān verses do not merely refer to eschatological justice but also serve as a fundamental principle for ecological equilibrium that must be maintained by humans as khalīfah. This Islamic ecotheological paradigm integrates theological awareness with ethical responsibility, positioning nature as an integral part of human existence rather than a mere object of exploitation. The novelty of this research lies in the synthesis between the metaphysical concept of mīzān and contemporary ecological ethics, providing a spiritual-preventive solution to environmental damage. These findings imply that internalizing the values of mīzān can strengthen environmental conservation efforts through a religious-holistic paradigm.